CERVICAL CANCER SCREENING KNOWLEDGE AND UTILISATION AMONG RURAL WOMEN IN IFE EAST LOCAL GOVERNMENT AREA OF OSUN STATE IN NIGERIA - Olowokere, A.E.; Ojo, MI.I. (Africa Journal of Nursing and Midwifery, 2016)
Cervical cancer is a deadly disease claiming the lives of many women in developing countries due to late presentation which might be influenced by a lack of knowledge of the disease and its prevention. This descriptive study examined the knowledge of rural women about cervical cancer and its prevention, and their utilisation of Pap smear screening, using a convenience sample of 426 women in Ife East Local Government Area of Osun State, Nigeria. Women voluntarily completed an unstructured questionnaire through trained research assistants. Results showed that women who participated in the study were aware of cervical cancer (77%; n=328) but many (62.9%; n= 268) were unaware of Pap smears as the screening tests for cervical cancer. Although 41.3% (n=176) were knowledgeable about cervical cancer, risk factors and prevention, only 9.4% (n=40) had Pap smear tests done. Health care professionals, especially community health nurses, need to intensify efforts to increase awareness about cervical cancer screening, and encourage women through the different clinics to use these services. The benefits of screening and early diagnosis of cervical cancer should be emphasized to enhance the utilization of cervical cancer screening services.